2016
DOI: 10.1177/0886260516683177
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Father Dyad Conflict Strategy Clusters: Implications for Emerging Adults

Abstract: Research has examined the different parenting styles that are present during emerging adulthood; however, less is known about potential parental conflict strategies that emerging adults may be experiencing during this developmental time period. Conflict strategies are conceptualized in the current study as parents' efforts to regulate, correct, or enforce a consequence in response to their emerging adult child's behavior. Previous research on discipline during childhood and adolescence has suggested the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Although this finding is somewhat surprising, it is consistent with rates found in recent studies that examined continued parental discipline practices during emerging adulthood. For example, in a study conducted by McKinney, Walker, and Kwan (2020), 59% of emerging adults surveyed endorsed receiving physical punishment from their father within the past year. In another study, 20% of emerging adult males and 17% of females reported experiencing corporal punishment (Pollard & McKinney, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this finding is somewhat surprising, it is consistent with rates found in recent studies that examined continued parental discipline practices during emerging adulthood. For example, in a study conducted by McKinney, Walker, and Kwan (2020), 59% of emerging adults surveyed endorsed receiving physical punishment from their father within the past year. In another study, 20% of emerging adult males and 17% of females reported experiencing corporal punishment (Pollard & McKinney, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Not only do emerging adults retain the knowledge they observed from their childhood, many are still receiving discipline from their parents which serves to further influence how emerging adults are likely to parent and discipline their children (McKinney, Walker, & Kwan, 2020; Nelson, Padilla-Walker, Christensen, Evans, & Carroll, 2011). Emerging adulthood is a unique developmental time period in which individuals are transitioning from a dependent to a more independent lifestyle (Arnett, 2000).…”
Section: Emerging Adults and Acceptability Of Corporal Punishmentmentioning
confidence: 99%
“…The current study examined conflict tactics similarly as Renk et al (2006); however, the participants in the current study were asked to not report retrospectively but rather only report current (i.e., past year) conflict tactics, involvement, and regard for their parents. Recent research on physical and psychological maltreatment perpetrated by parents reported by emerging adults over the past year indicated that a significant proportion of participants endorsed both physical and psychological tactics used against them (McKinney, Stearns, & Szkody, 2018; McKinney, Walker, & Kwan, 2016; Pollard & McKinney, 2016; Rogers, McKinney, & Asberg, 2018). For example, approximately 23% of females and 36% of males endorsed receiving a form of physical maltreatment from their father within the past year (McKinney et al, 2016), and emerging adults tended to report higher amounts of maternal, compared with paternal, maltreatment, with males who reported higher amounts of maltreatment than females (McKinney et al, 2018).…”
Section: Conflict Tactics During Emerging Adulthoodmentioning
confidence: 99%
“…Recent research on physical and psychological maltreatment perpetrated by parents reported by emerging adults over the past year indicated that a significant proportion of participants endorsed both physical and psychological tactics used against them (McKinney, Stearns, & Szkody, 2018; McKinney, Walker, & Kwan, 2016; Pollard & McKinney, 2016; Rogers, McKinney, & Asberg, 2018). For example, approximately 23% of females and 36% of males endorsed receiving a form of physical maltreatment from their father within the past year (McKinney et al, 2016), and emerging adults tended to report higher amounts of maternal, compared with paternal, maltreatment, with males who reported higher amounts of maltreatment than females (McKinney et al, 2018). Nelson et al (2011) highlighted that information regarding the impact of emerging adults’ relationships with their parents is limited; however, previous research focusing on childhood and later adolescence has suggested distinct and important differences regarding emerging adulthood and that further examination is needed.…”
Section: Conflict Tactics During Emerging Adulthoodmentioning
confidence: 99%
“…A large body of evidence suggests that harsh parenting has a strong impact on child outcomes (Baumrind, 1989; Gryczkowski et al, 2010; Jansen et al, 2012; Karazsia & Wildman, 2009; McKee, Colletti, Rakow, Jones, & Forehand, 2008; McKinney, Walker, & Kwan, 2016). For example, negative parenting (i.e., harsh discipline, overreactivity, laxness, and displays of anger) during childhood, regardless of consistency, predicted an increased risk of externalizing and internalizing problems in children between the ages of 2 and 25 years (Baumrind, 1989; Jansen et al, 2012; Karazsia & Wildman, 2009; McKinney & Brown, 2017; McKinney, Stearns, & Szkody, 2018; McKinney, Morse, et al, 2016), although harsh discipline in particular has not been shown to differentiate between internalizing and externalizing behavior problems (McKee et al, 2008; McKinney, Walker, et al, 2016).…”
Section: Parental Depression Harsh Parenting and Child Outcomesmentioning
confidence: 99%